Managing knowledge claims in classroom discourse: the public construction of a homogeneous epistemic status. Issue 2 (4th May 2017) - Heller, Vivien
Abstract: Drawing on sequential and multimodal analysis of video-recorded classroom interactions, the paper examines in detail the interactional practices and verbal and bodily displays that serve to (re-)establish a congruency between the teacher's expectation with regard to the participants' relative knowledge and the students' actual knowledge claims. By analysing the details of turn and action design, the present study shows how inserted knowledge questions and inserted knowledge accounts are used not to ascertain, but rather to define the students' epistemic status in a homogenising way. Challenging the students' knowledge, withholding confirmation and producing first explanations are practices that serve to reconstitute the students' limited access to new matters. Category-bound epistemic rights and obligations rather than displayed knowledge thus provide the basis for categorisations such as 'novices' or 'advanced learners'. It is argued that the public construction of a homogeneous epistemic status is consequential for the achievement of tasks and practical purposes in the multiparty setting of the classroom. Transforming individual students into a group of homogeneous novices enables participants to mutually align their knowledge claims and to form an epistemic ecology in which collective learning can take place.